Glutamine alleviates heat stress-induced impairment of intestinal morphology, intestinal inflammatory response, and barrier integrity in broilers. (11th July 2018) - Wu, Q J; Liu, N; Wu, X H; Wang, G Y; Lin, L
Abstract: The aim of this study was to investigate the protective effect of glutamine (Gln) on the intestinal morphology, intestinal inflammatory response, and barrier integrity in broilers exposed to high ambient temperature. Three-hundred-sixty 21-d-old Arbor Acres broilers (half male and half female) were randomly allocated to 4 treatment groups in a completely randomized design, each of which included 6 replicates with 15 birds per replicate, for 21 d. The 4 treatment groups were as follows: the control group, in which birds were kept in a thermoneutral room at 22 ± 1°C (no stress, NS; fed a basal diet); the heat stress group (36 ± 1°C for 10 h/d from 08:00 to 18:00 h and 22 ± 1°C for the remaining time, heat stress (HT ); fed a basal diet); and heat stress + Gln group (0.5 and 1.0% Gln, respectively). Compared to the NS group, broilers in the HT group had lower villus height ( P < 0.05), higher crypt depth ( P < 0.05), higher D-lactic acid and diamine oxidase (DAO) activity ( P < 0.05), higher soluble intercellular adhesion molecule-1 (sICAM-1) concentration ( P < 0.05), higher tumor necrosis factor (TNF)- α /interleukin (IL)-10 ( P < 0.05), and lower tight junction protein expression levels ( P < 0.05). Compared with birds in the HT, birds in the HT + Gln group exhibited increased villus height ( P < 0.05), decreased D-lactate and DAO activity ( P < 0.05), decreased sICAM-1 concentration ( P < 0.05), and mediate the secretion of cytokines ( P < 0.05), as well as increased zonula occludens-1 (ZO-1), claudin-1, and occludin mRNA expression levels ( P < 0.05). In conclusion, these results indicate that supplementation with Gln was effective in partially ameliorating the adverse effects of heat stress on intestinal barrier function in broilers by promoting epithelial cell proliferation and renewal, modifying the function of the intestinal mucosa barrier, and regulating the secretion of cytokines.